2019
DOI: 10.3389/fneur.2019.01118
|View full text |Cite
|
Sign up to set email alerts
|

A Visual Task Management Application for Acute Ischemic Stroke Care

Abstract: Background: To maximize the effect of intravenous (IV) thrombolysis and/or endovascular therapy (EVT) for acute ischemic stroke (AIS), stroke centers need to establish a parallel workflow on the basis of a code stroke (CS) protocol. At Kokura Memorial Hospital (KMH), we implemented a CS system in January 2014; however, the process of information sharing within the team has occasionally been burdensome.Objective: To solve this problem using information communication technology (ICT), we developed a novel applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
1
1
Order By: Relevance
“…The favorable outcome rate was very high in both of the present groups compared with those reported previously [9,22]. Previous studies have reported that in-hospital medical apps [15,20], telestroke evaluation [23], and treatment by a mobile stroke unit [23,24] reduced DNT, but to the best of our knowledge, none studied the relationship between favorable outcome and improvements in the stroke care system.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The favorable outcome rate was very high in both of the present groups compared with those reported previously [9,22]. Previous studies have reported that in-hospital medical apps [15,20], telestroke evaluation [23], and treatment by a mobile stroke unit [23,24] reduced DNT, but to the best of our knowledge, none studied the relationship between favorable outcome and improvements in the stroke care system.…”
Section: Discussioncontrasting
confidence: 46%
“…Furthermore, it has been suggested that this digitization process may be accelerated in the stroke care after a global emergency represented by the COVID-19 pandemic [13]. Already, several stroke centers have trialed a medical information and communication technology (ICT) smartphone applications [14,15] with the aim of shortening IV-tPA and MT times from onset. These applications perform task management and time tracking for reperfusion therapy, and present this information visually for sharing among the stroke team.…”
Section: Introductionmentioning
confidence: 99%
“…This likely reflects that dashboards have become part of the growing burden of administrative responsibilities clinicians face [217,218]. We also found with the growth in dashboards, end users have expanded to include entire clinical teams (e.g., rapid response teams [51,111,157], care teams completing patient rounds[29,56,113]), and even patients, who often input symptoms or vital signs to supplement EHR data [104,115,147,167,171,174], reflecting the growing complexity of health care teams and trends in patient reported outcomes.…”
Section: Principal Findings and Comparison With Prior Workmentioning
confidence: 91%
“…Verschiedene Konzepte zur Qualitätskontrolle, wie regelmäßige Nachbesprechungen der Thrombolysen bzw. App-basierte Konzepte zur Dokumentation der Prozesszeiten konnten in Studien die Wirksamkeit belegen [88][89][90].…”
Section: Prozessoptimierung Der Innerklinischen Schlaganfallakutversounclassified